Navigating the financial blogosphere : - Bailyn, Russell (John Wiley & Sons, 2007)
Financial information on the Internet has exploded in volume; the challenge is to find what's useful and reliable. Russell Bailyn's book does an excellent job of presenting important personal finance topics in a clear and digestible form, and pointing readers to a wealth of high-quality sources on the Internet. Navigating the Financial Blogosphere is browsable, fun, and very useful. Russell Bailyn not only explains financial decision making, but like a good research librarian, he tells you where to go on the Web for more information. You'll want to be close to your computer as you read this book.